Frontal Cystic Meningioma Removed by a Partial Transfrontal Craniotomy in a Cat - Kim, Kihoon (Acta Scientiae Veterinariae, 2021)
Background: Meningiomas are the most frequently reported intracranial tumors in cats. It is known to arise at the point of arachnoid cells project into the dural venous sinuses. Cats with intracranial meningiomas are treated by surgical management as the tumors are commonly delineated from normal brain tissue and are not likely to adhere to the cerebral parenchyma. Although meningioma is the most common intracranial tumor in cats, the incidence of cystic meningioma is low. The objective of the current study is to report a case of frontal cystic meningioma with peritumoral cystic structure removed by a partial transfrontal craniotomy. Case: A 10-year-old castrated British shorthair cat was referred to the Baeksan Feline Medical Center with a recent onset of seizures. On the physical examination, the patient was bright and alert. Neurological examinations were unremarkable at the time of presentation. Hematologic examinations were within normal limits. Thoracic and abdominal radiography, and abdominal ultrasonography revealed unremarkable findings. Magnetic resonance imaging revealed an extra-axial mass cranial to the frontal lobe. On the sagittal plane, a cystic structurewas identified in the frontal areaon post-contrast T1W images. No contrast enhancement of the cystic wall was identified after intravenous injection of contrast medium on T1W. On the transverse plane of T2W images, midline shift to the left due to peritumoral edema was observed. The mass was removed via partial transfrontal craniotomy. Postoperative radiography was performed to ensure appropriate placement of the mesh. The patient recovered uneventfully after anesthesia. After the surgery, the patient was closely monitored in an intensive care unit between 24 and 48 h. Based on the histologic findings, the final diagnosis was a fibroblastic meningioma. Nineteen months after the surgery, there was no seizure activity identified by the owner. Discussion: Depending on the location of the cyst, meningiomas can be classified into 4 types according to the human literature. In types 1 and 2, the whole cyst is located within the tumor, resulting in contrast enhancement of the cystic wall. In types 3 and 4, the cysts are located outside the tumor, and no contrast enhancement of the cystic wall is observed. In type 3, the cyst lies adjacent to the brain parenchyma rather than adjacent to the tumor and the meningioma is related to a cerebrospinal fluid cyst bordered by the arachnoid. It is important to classify the type of cystic meningioma prior to surgery in order to decide whether to remove the cystic wall. In type 2, the cystic wall is infiltrated by tumor cells, while the cystic wall of type 3 meningioma is composed of gliotic tissue without any tumor cells. Therefore, in type 2, the meningiomas with cystic walls should be removed for the prevention of recurrence, while in type 3 meningioma, the tumor can be managed by cyst decompression and excision of the solid component. Based on the Nauta classification, the cystic meningioma reported here was considered to be type 3. Therefore, the surgical procedure aimed to remove the solid component of the mass, leaving the cystic wall attached to the normal brain. As the solid part of the meningioma was located beneath the internal plate of the left frontal bone, the partial transfrontal craniotomy was sufficient to expose and remove the entire mass. To the author’s knowledge, this is first case report describing a patient with frontal meningioma with a peritumoral cyst removed by a partial transfrontal craniotomy based on the Nauta classification.